Strategi Media Relations PT Kereta Api Indonesia (KAI Commuter) dalam Menangani Krisis Komunikasi Terkait Kasus Pelecehan Seksual Penumpang KRL di Jabodetabek - Wulandari, Charisma Dina; Ayuningtyas, Fitria (Universitas Batanghari Jambi, 2024)
The purpose of this study is to determine whether the strategy of PT Kereta Api Indonesia Commuter (KAI Commuter) in improving public information facilities for sexual harassment cases on the Jabodetabek KRL is effective. The method used in solving this problem is the Descriptive Qualitative Method. with qualitative content analysis method. With 7 responses from KRL passengers in Jabodetabek who use KRL at least 2x in 1 week. Based on research using qualitative content analysis, it is found that PT Kereta Api Indonesia Commuter (KAI Commuter) uses a media relations strategy by hoping to reduce a lot of justification. This means that PT Kereta Api Indonesia Commuter (KAI Commuter) tends to try to take full responsibility for the occurrence of sexual harassment by confirming to the mass media and immediately taking action against the perpetrator and providing support to victims psychologically.